The Challenge of Religious Moderation amidst the Rise of Religious Extremism among Instant Ustadz in Indonesia - Akhmad Ainur Roziqin; Yasinatul, Puspa Arum; Ali Mursyid Azisi; Luluk Fikri Zuhriyah; Moh. Hakim Alfarisi (Al-Wasatiyah: Journal of Religious Moderation, 2025)
The issues of arrogance, religious extremism, and misunderstanding of Islamic teachings are serious problems that have the potential to disrupt socio-religious stability. This article explicitly explores the recent proliferation of instant preachers (ustadz) who lack a profound comprehension of religion, a moderate sanad, and an intellectualist interpretation of religion. Ultimately, these groups exhibit signs of religious arrogance, encompassing the practice of takfīr, the assertion of supremacy, and a proclivity for advocating discrimination over violence. The writing of this article uses a qualitative method of descriptive critical analysis and literature study. The main data refers to the findings of virtual observations related to the rampant phenomenon of arrogant instant preachers, then data from surveys by specialized institutions that study extreme religious movements on social media, and selected interviews with various parties. The findings of this article indicate that individuals who acquire a comprehensive understanding of religion without the guidance of a qualified and tempered instructor are susceptible to developing an exaggerated sense of self-importance, which can manifest in religious extremism. With its takfirī characteristics and often legalizing violence, this is a serious problem, especially for preachers in Indonesia. This article can be academically useful in the field of religious pattern studies in Indonesia. Practically, it is expected to get a response from the Ministry of Religious Affairs, the National Council for Religious and Cultural Affairs (BPNT), Indonesian Ulema Council's Countering Extremism and Terrorism Agency (BPET-MUI), and moderate religious organizations Nahdlatul Ulama (NU) and Muhammadiyah to pay more attention to the emergence of new preachers who have sprung up on social media with backgrounds and religious understanding that are far from the competency standards of mastery of religious knowledge.